2003
DOI: 10.1094/phyto.2003.93.7.853
|View full text |Cite
|
Sign up to set email alerts
|

Amplified Fragment Length Polymorphism Diversity in Cephalosporium maydis from Egypt

Abstract: Cephalosporium maydis, the causal agent of late wilt of maize, was first described in Egypt in the 1960s, where it can cause yield losses of up to 40% in susceptible plantings. We characterized 866 isolates of C. maydis collected from 14 governates in Egypt, 7 in the Nile River Delta and 7 in southern (Middle and Upper) Egypt, with amplified fragment length polymorphism (AFLP) markers. The four AFLP primer-pair combinations generated 68 bands, 25 of which were polymorphic, resulting in 52 clonal haplotypes tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 12 publications
1
21
0
2
Order By: Relevance
“…Zeller et al [19] identified four AFLP primer pairs that could be used as markers to determine the distribution of H. maydis lineages and to identify new lineages in field populations. Here, we used this H. maydis-unique nucleotide sequence, which proved earlier to be species-specific [17], as a diagnostic tool. As previously described [9], the pathogen spreads in moderately resistant Royalty cv.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zeller et al [19] identified four AFLP primer pairs that could be used as markers to determine the distribution of H. maydis lineages and to identify new lineages in field populations. Here, we used this H. maydis-unique nucleotide sequence, which proved earlier to be species-specific [17], as a diagnostic tool. As previously described [9], the pathogen spreads in moderately resistant Royalty cv.…”
Section: Discussionmentioning
confidence: 99%
“…This new sequence is a major part of a larger AFLP fragment that was proven earlier to be species-specific [9,17,19]. The A200a primer set-[A200a-for (forward primer): 5'-CCTAGTA-GTCCCGACTGTTAGG-3', A200a-rev (reverse primer): 5'-TTGGTTCACCGTCTTTTGTAGG-3'] amplifies a specific [14] H. maydis segment.…”
Section: Adaptation Of Molecular Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…The Egyptian, Indian and Hungarian isolates of H. maydis differ in morphology, pathogenicity and route of infection (Warren 1983). In Egypt, there are four clonal lineages of H. maydis that differ in colonization ability and virulence on maize (El-Assiuty et al 1999;Saleh et al 2003;Zeller et al 2000Zeller et al , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Marcadores fundamentados em diferenças na molécula de DNA são mais eficientes na detecção de diversidade genética. Mais recentemente, a técnica baseada na amplificação de polimorfismo de comprimento via reação em cadeia da polimerase (AFLP -Amplified fragment length polymorphisms) vem sendo utilizada para estudos desta natureza em diversos organismos (Müeller & Wolfenbarger, 1999), entre eles os fungos fitopatogênicos (Majer et al, 1998;Wang et al, 1998;Dunkle & Levy, 2000;Borie et al, 2002;Tooley et al, 2002;Saleh et al, 2003). Esta técnica combina a especificidade, a resolução e o poder de amostragem genômica das enzimas de restrição com a rapidez e praticidade da detecção de polimorfismos da PCR (Ferreira & Grattapaglia, 1995).…”
Section: Métodos Moleculares Para Detecção De Diversidade Genéticaunclassified